2013
DOI: 10.1016/j.astropartphys.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo design studies for the Cherenkov Telescope Array

Abstract: The Cherenkov Telescopes Array (CTA) is planned as the future instrument for very-high-energy (VHE) gamma-ray astronomy with a wide energy range of four orders of magnitude and an improvement in sensitivity compared to current instruments of about an order of magnitude. Monte Carlo simulations are a crucial tool in the design of CTA. The ultimate goal of these simulations is to find the most cost-effective solution for given physics goals and thus sensitivity goals or to find, for a given cost, the solution be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
365
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(365 citation statements)
references
References 41 publications
0
365
0
Order By: Relevance
“…Given that variability of one order of magnitude or even larger is often observed in the X-ray and TeV bands, most of the HSP blazars in our sample (with the exception of those at very high redshift) may be detectable during flaring episodes by the present generation of Cherenkov telescopes, and certainly by the future CTA, as shown in Fig. 14. There we present the SED of 1WHSP J172504.3+115215 and compare the sensitivities of Fermi-LAT (for a four year exposure) and CTA (for a 50 h exposure Bernlöhr et al 2013), which are approximately equivalent at the energy of 50 GeV.…”
Section: The Infrared Log N-log S Of Hsp Blazarsmentioning
confidence: 99%
“…Given that variability of one order of magnitude or even larger is often observed in the X-ray and TeV bands, most of the HSP blazars in our sample (with the exception of those at very high redshift) may be detectable during flaring episodes by the present generation of Cherenkov telescopes, and certainly by the future CTA, as shown in Fig. 14. There we present the SED of 1WHSP J172504.3+115215 and compare the sensitivities of Fermi-LAT (for a four year exposure) and CTA (for a 50 h exposure Bernlöhr et al 2013), which are approximately equivalent at the energy of 50 GeV.…”
Section: The Infrared Log N-log S Of Hsp Blazarsmentioning
confidence: 99%
“…Equations 7 and 8 will be used for adding noise to the simulated data presented in Section 4. If we assume individual CTA telescope areas of ∼ 43 m 2 (roughly ∼ 3.7 m dishes consistent with Bernlöhr et al (2013)), an electronic bandwidth of ∼ 2 GHz, a quantum efficiency of ∼ 60%, λ = 545 nm, and an optical bandwidth of ∼ 10 11 s −1 for 50 hrs of observing time on a 3 rd magnitude star (corresponding to n ∼ 10 −5 m −2 s −1 Hz −1 , depending on stellar temperature), we obtain SN R (2) ∼ 2000 and a SN R (3) ∼ 3. Both SN R (2) and SN R (3) can benefit from using multiple spectral channels since the SN R improves as the square root of the number of spectral channels.…”
Section: Signal-to-noisementioning
confidence: 99%
“…Then we take the Fast Fourier Transform (FFT) of the pristine image, and sample the data in the (u, v) plane as determined by the telescope array configuration and the observing wavelength. A possible CTA array configuration (Bernlöhr et al 2013) is shown in Figure 2, consisting of 74 telescopes of 4 m and 7 m telescopes, spread out over 2 kilometers. Such an array provides 2701 baselines pairs, ranging from 14 m to 2 km, and 70300 telescope triplets.…”
Section: Simulation Of Intensity Interferometry Datamentioning
confidence: 99%
“…In this study we focus on the impact of the performance of the CTA observatory on the determination of the spectral parameters of the sources we have studied in the previous section, comparing the SEDs that we obtained with the Fermi -LAT and the SEDs that we would expect from CTA. For this section we make use of instrument response functions for a preliminary design of the southern array 9 , based on the study of Bernlöhr et al (2013). We highlight that these IRFs are still very preliminary as the observatory is not yet in place.…”
Section: Future Potential Of Ground Based Instrumentsmentioning
confidence: 99%